2020
DOI: 10.1038/s41598-020-59853-z
|View full text |Cite
|
Sign up to set email alerts
|

Activated FGF2 signaling pathway in tumor vasculature is essential for acquired resistance to anti-VEGF therapy

Abstract: Anti-vascular endothelial growth factor (VEGF) therapy shows antitumor activity against various types of solid cancers. Several resistance mechanisms against anti-VEGF therapy have been elucidated; however, little is known about the mechanisms by which the acquired resistance arises. Here, we developed new anti-VEGF therapy-resistant models driven by chronic expression of the mouse VEGFR2 extracellular domain fused with the human IgG4 fragment crystallizable (Fc) region (VEGFR2-Fc). In the VEGFR2-Fc-expressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 58 publications
(36 reference statements)
0
23
1
1
Order By: Relevance
“…Ichikawa et al reported that in cell lines and in an animal model that acquired resistance to anti-VEGF-based therapy is associated with a similar over-expression of both FGF-2 and vascular endothelial growth factor receptor-2 (FGFR-2). Tumor over-expressing the mouse VEGFR2 extracellular domain fused with the human IgG4 fragment crystallizable (Fc) region (VEGFR-2-Fc) showed highest levels of mRNA expression from FGF2 and other factors of FGF-2/FGFR-2 pathway [34]. Finally, in ovarian cancer resistant to bevacizumab, Guerrouehan et al demonstrated that Protein Kinase B (PKB also known as AKT)-mediated endothelial factors secretion (where FGF-2 plays a major role) creates an autocrine loop that avoids bevacizumab inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Ichikawa et al reported that in cell lines and in an animal model that acquired resistance to anti-VEGF-based therapy is associated with a similar over-expression of both FGF-2 and vascular endothelial growth factor receptor-2 (FGFR-2). Tumor over-expressing the mouse VEGFR2 extracellular domain fused with the human IgG4 fragment crystallizable (Fc) region (VEGFR-2-Fc) showed highest levels of mRNA expression from FGF2 and other factors of FGF-2/FGFR-2 pathway [34]. Finally, in ovarian cancer resistant to bevacizumab, Guerrouehan et al demonstrated that Protein Kinase B (PKB also known as AKT)-mediated endothelial factors secretion (where FGF-2 plays a major role) creates an autocrine loop that avoids bevacizumab inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 is also overexpressed in subtypes of bladder cancer, and is associated with promoting migration, angiogenesis and invasiveness [ 141 , 142 ]. FGF2 expression by tumor vasculature pericytes has also been identified as a mechanism of anti-vascular endothelial growth factor receptor (VEGFR) resistance [ 143 ]. FGF2 is an angiogenic factor in multiple myeloma (MM) that positively regulates expression of growth and survival interleukin-6 (IL-6) in a reciprocal manner [ 144 ].…”
Section: Fgf Signaling Diversity In Cancermentioning
confidence: 99%
“…Additionally, VEGF xxx b isoforms inhibits the angiogenic activity of VEGF and may be effective in anti-cancer therapy [ 186 ]. In a study using VEGFR2-Fc-resistant murine melanoma models, the FGF2 signaling pathway was found to play a key role between endothelial cells and pericytes in maintaining tumor vasculature in acquired anti-VEGF-resistant tumors [ 187 ].…”
Section: Vegfrmentioning
confidence: 99%